2018
DOI: 10.1016/j.bbamem.2018.02.026
|View full text |Cite
|
Sign up to set email alerts
|

pH sensing by lipids in membranes: The fundamentals of pH-driven migration, polarization and deformations of lipid bilayer assemblies

Abstract: Most biological molecules contain acido-basic groups that modulate their structure and interactions. A consequence is that pH gradients, local heterogeneities and dynamic variations are used by cells and organisms to drive or regulate specific biological functions including energetic metabolism, vesicular traffic, migration and spatial patterning of tissues in development. While the direct or regulatory role of pH in protein function is well documented, the role of hydrogen and hydroxyl ions in modulating the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(46 citation statements)
references
References 171 publications
(314 reference statements)
0
43
0
Order By: Relevance
“…It has been shown that pH gradients induce surface tension asymmetry, cause shape deformations and induce the formation of membrane invaginations reminiscent of mitochondrial cristae. [ 41 ]…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that pH gradients induce surface tension asymmetry, cause shape deformations and induce the formation of membrane invaginations reminiscent of mitochondrial cristae. [ 41 ]…”
Section: Discussionmentioning
confidence: 99%
“…The group of Angelova [ 53 ] has deeply studied the effect of pH changes on giant unilamellar vesicles (GUV). They demonstrated that a pH change induces deformations of the whole vesicle, as well as vesicle migration and polarization in membranes with phase separated lipid domains.…”
Section: Ph Effectsmentioning
confidence: 99%
“…Interesting, local pH-induced tubulation is regulated by the lipid composition of the membrane. A very complete review of the experimental results and the related model has been published by the group [ 53 ], and thus, we recommend its reading instead of going deeper in this topic here. Related to mitochondrial membranes, we also recommend the review about the architecture and functions of mitochondrial cristae by F. Joubert and N. Puff that appear in this special issue.…”
Section: Ph Effectsmentioning
confidence: 99%
“…2), the biological relevance of a low pH mechanism in regulating profilin/actin dynamics is not fully established. In motile cells, the pH gradients formed by the asymmetric distribution of NHE1 along the axis of movement of cells change from pH 7.6 to 6.9 from leading to trailing edges (Martin et al 2011;Angelova et al 2018) and so are still too high. The cytosol of apoptotic cells decreases to pH 5.7 due to H + ions released from lysosomes (Nilsson et al 2006).…”
Section: Regulation Through Phmentioning
confidence: 99%